Of jaguars and butterflies : metalogues on issues in anthropology and philosophy - Lloyd, G. E. R. (Geoffrey Ernest Richard), 1933-; Vilaça, Aparecida, 1958- (Berghahn Books, 2023)
"What are we to make of statements that jaguars see themselves as humans, or of doubts about the boundary between dreams and waking? Jointly authored by an anthropologist and a philosopher, this book investigates some of the most puzzling ideas and practices reported in modern ethnography and ancient philosophy, concerning humans, animals, persons, spirits, agency, selfhood, consciousness, nature, life, death, disease and health. The study's twin aims are first to explore the possibility of achieving a better understanding of the materials we discuss and then to see what lessons we can draw from them to challenge and revise our own fundamental assumptions"-- Provided by publisher.
Keywords: Philosophical anthropology.; Anthropologie philosophique.; philosophical anthropology.; SOCIAL SCIENCE / Anthropology / Cultural & Social; Philosophical anthropology